A novel porous carbon material derived from the byproducts of bean curd stick manufacture for high-performance supercapacitor use. Issue 70 (29th November 2018) - Shi, Lulu; Jin, Lihua; Meng, Zheng; Sun, Yanan; Li, Cong; Shen, Yehua
Abstract : Preparation of heteroatom-functionalized porous carbon derived from byproducts of bean curd stick manufacture as an electrode material for high performance supercapacitors. Abstract : The exploitation of efficient renewable energy resources and the promotion of added value of agricultural products are always hot topics. In this study, we present a novel porous carbon material for high performance supercapacitor applications made from the byproduct of bean curd stick manufacture. The as-prepared carbon material possesses a hollow interconnected structure with a large specific surface area (2609 m 2 g −1 ), while containing 5.01% oxygen and 1.75% nitrogen heteroatoms. Therefore, besides electrical double-layer capacitance, it can also produce additional pseudocapacitance to enhance the overall capacitance. Benefiting from these advantages of structure and composition, the bean curd stick based porous carbon material demonstrates a high specific capacitance of 405 F g −1 at 0.5 A g −1 . Moreover, the presented porous carbon material based symmetric supercapacitor also offers a high energy density (11.35 W h kg −1 at a power density of 125 W kg −1 ). All the above findings indicate that the byproduct of bean curd stick manufacture is an excellent optional material for preparing high-performance supercapacitor material. Simultaneously, this work also provides an effective strategy for adding value to agricultural products.